Language proficiency and competence: upper elementary students in a Dual-Language Bilingual Education program. Issue 6 (3rd July 2022) - He, Shuhua; Yang, Lu; Leung, Genevieve; Zhou, Qing; Tong, Rosina; Uchikoshi, Yuuko
ABSTRACT: Building on research that has demonstrated the benefits of Dual-Language Bilingual Education (DLBE) programmes on students' bilingual, academic, and cross-cultural development (Lindholm-Leary and Hernández 2011), this study examines the links between dual language proficiency and competence in elementary students enrolled in a Cantonese DLBE programme in the U.S. Specifically, we examined the relations between (a) children's bilingual (English and Cantonese) language proficiency in four dimensions (reading, writing, listening, and speaking) and (b) their competence in academic, peer relationships, activities involvement, and classroom behaviour domains with a group of 60 fourth and fifth graders enrolled in a Cantonese–English DLBE programme. Multiple regression results show that both Cantonese speaking and writing proficiency had significant main effects on academic competence. These effects remained significant even after controlling for students' English speaking/writing proficiency. Moreover, both Cantonese and English writing proficiency were positively related to students' classroom competence. Additionally, higher English reading proficiency was positively associated with peer competence. Results highlight the different beneficial roles of Cantonese and English proficiency on positive self, peer acceptance, and prosocial behaviour. The current study generates new insights into the role of bilingual proficiency and has implications for DLBE programme curriculum and policy. 本文探讨了在美国就读英粤语双向式双语课程的小学生的双语熟练程度及其能力发展之间的关系。 我们研究了60名就读该课程的四及五年级儿童的 (a)英语和粤语语言能力 (阅读、写作、听力和口语) 和他们的 (b) 学术、同伴交往、活动参与课堂自我管理能力之间的关系。结果表明, 粤语口语和写作能力对学业能力具有显著的影响。粤语和英语写作能力与学生的课堂能力呈正相关。此外, 较高的英语阅读能力与同伴交往能力呈正相关。本研究反映了粤语和英语能力对积极的自我观念、同伴接纳和利社会行为的有益作用, 并为双向式双语课程和政策的发展提供了参考。